Analysis of Mixture Formation and Flame Development in Biodiesel Burner Combustion Using Direct Optical Visualization Technique - Amir, Khalid; M. D., Anuar; M. Farid, Sies; B., Manshoor; Izzuddin, Zaman; Abdul Adam, Abdullah; R., Mamat (Trans Tech Publications Inc., 2014)
Despite years of emission-reduction attempts, biodiesel combustion still have problem of emitting NOx, CO and particulate matter (PM) into the atmosphere. To reduce emissions, the improvements throughout the combustion process have been considered with the enhancement fuel-air mixing. Optical visualization technique is very essential due to its ability to record real time color image of fuel-air premixing and flame development during burning process. The purpose of this study is to determine the relation between mixture formation and flame development of burner combustion using optical visualization technique and image processing technique. Blending of biodiesel ratio was varied from 5 vol% (B5) – 15 vol% (B15). Water content under emulsified biodiesel was varied up to 15 percent, and equivalence ratio from 0.6 to 2.0. The real spray image of emulsified biodiesel and different equivalence ratio were captured by direct photography method together with color digital camera. The images of the spatial distribution of fuel-air mixing and natural flame luminosity will be further analyzed and to obtain information of the flame development in order to understand the influences of fuel-air premixing on combustion process and burning process. Analysis of spray evaporation and observations of combustion process reveal that the mixture formation exhibit influences to the ignition process and flame development.